Beberapa Faktor yang Mempengaruhi Pendapatan dan Efisiensi Ekonomi Usaha Peternakan Kambing Rakyat di Kecamatan Kradenan Kabupaten Grobogan - Achmad Nur Chamdi (Caraka Tani: Journal of Sustainable Agriculture, 2003)
The aims of the research were to know income and economic efficiency level of smallholder goat farming, and to know the factors affecting them. The research was held on April 12th-24th, 2000. The research was done using survey method and the samples were taken by purposive random sampling. Total respondents are 200 farmers. The research variables were income level (Y1) and economic efficiency (Y2) as dependent variables, and the independent variables were the number of goat owned, feed cost, farmer’s age, farmer’s education level, breeding experience, farming system, and farmer’s main job. The data are analyzed using multiple regression analysis with Cobb-Douglas production function model, F-test and t-test. The results of this research showed that income level of smallholder goat farming in Kradenan Subdistrict, Grobogan Regency is Rp.338.323,00 per year per farmer and economic efficiency level is 2,20. The socio-economic factors such the number of goat owned, feed cost, farmer’s age, farmer’s education level, breeding experience, farming system, and farmer’s main job altogether influence very significant (P<0,01) to income level and economic efficiency. Whereas partially, the number of goat owned, feed cost, breeding experience and farmer’s man job influence very significant (P<0,01) to income level, and the number of goat owned, feed cost and farming system influenced very significant (P<0,01) to economic efficiency.